1998
DOI: 10.1148/radiology.206.1.9423660
|View full text |Cite
|
Sign up to set email alerts
|

Uterine arteriovenous malformations: gray-scale and Doppler US features with MR imaging correlation.

Abstract: Gray-scale morphology and Doppler US features should allow noninvasive diagnosis of uterine AVMs. Doppler and MR imaging features of uterine AVMs may overlap with other causes of arteriovenous shunting, including abnormal placentation and gestational trophoblastic disease (GTD). These can be differentiated with serum beta human chorionic gonadotropin test results (negative with AVM, positive with GTD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
145
0
9

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 0 publications
3
145
0
9
Order By: Relevance
“…A baixa pressão do fluxo de saída causa discreta desaceleração durante a diástole, com diminuição da pulsatilidade do fluxo arterial. Por fim, o tortuoso aglomerado vascular apresenta rápida variação na direção do fluxo não observado nos vasos normais 18 . Estas caracterís-ticas vasculares fornecem os parâmetros clássi-cos que diagnosticam MAVU: diminuição do IR, diminuição do IP, aumento da VSM, com pequena variação nas velocidades sisto-diastólicas e tortuosidade vascular.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A baixa pressão do fluxo de saída causa discreta desaceleração durante a diástole, com diminuição da pulsatilidade do fluxo arterial. Por fim, o tortuoso aglomerado vascular apresenta rápida variação na direção do fluxo não observado nos vasos normais 18 . Estas caracterís-ticas vasculares fornecem os parâmetros clássi-cos que diagnosticam MAVU: diminuição do IR, diminuição do IP, aumento da VSM, com pequena variação nas velocidades sisto-diastólicas e tortuosidade vascular.…”
Section: Resultsunclassified
“…Nossa casuística apresentou IP médio de 0,44; IR médio de 0,36; VSM média de 64,6 cm/s, semelhante aos apresentados na série de nove casos de Timmerman et al 1 , cuja média de IP foi 0,45; IR de 0,37 e VSM de 56 cm/s, e aos dez casos descritos por Huang et al 18 , cuja variação de IP foi de 0,25-0,55; IR 0,3-0,6 com VSM superior a 96 cm/s.…”
Section: Resultsunclassified
“…In postoperative patients, AVM is believed to arise in the venous sinuses incorporated within myometrial scars. 9 Vascular malformations of the uterus such as endometrial aneurysm 10 and uterine AVMs 11 have been described previously. Although the grayscale morphologic features of these malformations are nonspecific, duplex Doppler sonography can accurately characterize the type of vascular abnormality as venous, arteriovenous, or arterial.…”
Section: Discussionmentioning
confidence: 99%
“…11 Past angiographic studies have demonstrated arteriovenous communications in 0.9% of normal uterine pregnancies, 20% of miscarriages and missed abortions, and 39% of ectopic pregnancies. 10,11 This shunting is thought to result from the development of arteriovenous fistulas within the placenta caused by necrosis of the chorionic villi. This theory explains the imaging findings seen in our case where arteriovenous communications developed late in the postpartum period, probably after the necrosis of the chorionic villi in the RPOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation